“Figuring it out on our own”: exploring family medicine residents’ sexual assault and domestic violence training - Keren, Daniela; Kelly, Martina; Wakabayashi, Adrienne; McNair, Susan (Canadian Medical Education Journal, 2022)
Background: Family physicians are uniquely able to provide comprehensive and longitudinal care to those experiencing sexual assault and domestic violence (SADV). To date, we know little about how Canadian family medicine (FM) residents learn about SADV. This study explored SADV teaching in residency from the perspectives of FM residents. Methods: This qualitative study took place in the Western University FM residency program. We conducted semi-structured interviews with first- and second-year FM residents (n=8). We analyzed data using thematic analysis. Results: We identified three inter-related themes: (1) Inconsistent training for SADV, (2) Attitudes towards SADV and (3) Learner hesitancy. Quality and quantity of SADV learning opportunities were inconsistent across learners, fuelling feelings of incompetence and lack of confidence around providing SADV care. This led to hesitant behaviours by learners when encountering SADV clinically. Conclusions: Understanding FM residents’ experiences and ideas regarding SADV education is critical in order to graduate physicians equipped to care for this vulnerable population. This research highlights the relationship among learners’ and teachers’ experiences, attitudes and behaviours; targeting this behavioural cycle may improve SADV learning.